2010
DOI: 10.1097/ccm.0b013e3181f8569b
|View full text |Cite
|
Sign up to set email alerts
|

Automated drug dispensing system reduces medication errors in an intensive care setting

Abstract: The implementation of an automated dispensing system reduced overall medication errors related to picking, preparation, and administration of drugs in the intensive care unit. Furthermore, most nurses favored the new drug dispensation organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 29 publications
3
125
0
2
Order By: Relevance
“…In Grenoble University Hospital, both the intensive care unit (ICU) and the haematology ward are now equipped with automated dispensing systems (ADSs). 9 Pharmacy technicians reload the ADS compartments on a daily basis using drug trolleys routed from the pharmacy to the ward.…”
Section: Introductionmentioning
confidence: 99%
“…In Grenoble University Hospital, both the intensive care unit (ICU) and the haematology ward are now equipped with automated dispensing systems (ADSs). 9 Pharmacy technicians reload the ADS compartments on a daily basis using drug trolleys routed from the pharmacy to the ward.…”
Section: Introductionmentioning
confidence: 99%
“…In UK hospital pharmacies, Franklin et al [11] showed that the implementation of ADS represents a 23% increase in storage capacity in the first site and a 123% increase in the second site, compared to traditional storage [7]. Installing ADS contributes to medication safety [3][4][5][6]11]. ADS ensures that drugs resources are secure, organized, tracked and ready for use.…”
Section: Discussionmentioning
confidence: 99%
“…Both systems are complementary. ADSs start to be widely established in hospital medication organization in Europe and especially in UK, and many studies have demonstrated their contribution to decrease iatrogenic injuries by reducing potentially preventable events [3][4][5][6]. But high cost of these available technologies must have to be considered regarding to the efficiency.…”
mentioning
confidence: 99%
“…7,8 When utilized with careful supervisory oversight, these devices have been shown to decrease medication administration errors. [9][10][11][12] For this reason, professional pharmacy organizations generally are supportive of implementation and utilization of ADCs in institutional patient care areas. 13 ADCs designed for use within the hospital pharmacy are likewise available (eg, NarcStation from Aesynt; Pyxis C II Safe from CareFusion).…”
Section: Electronic Inventory Systems and Barcode Technologymentioning
confidence: 99%